TYPES OF ORGANIZATION OF INDEPENDENT WORK IN PRACTICAL CLASSES. - Yulanova Nargiza Davlatovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation. The article describes the development of student’s independence and responsiveness during the practical classes. In case of continuous learning and self-development, it is very important to focus on evolving the independence, creativity and self-learning skills of the student. There are four levels of independent-learning judging by the nature of the student learning experience.